Incidence and 1-year outcome of periprocedural myocardial infarction following cardiac surgery: are the Universal Definition and Society for Cardiovascular Angiography and Intervention criteria fit for purpose?. (25th January 2022) - Hinton, Jonathan; Augustine, Maclyn; Gabara, Lavinia; Mariathas, Mark; Allan, Rick; Borca, Florina; Nicholas, Zoe; Ikwuobe, John; Gillett, Neil; Kwok, Chun Shing; Cook, Paul; Grocott, Michael P W; et al.
Abstract: OBJECTIVES: The diagnosis and clinical implications of periprocedural myocardial infarction (PPMI) following coronary artery bypass grafting (CABG) are contentious, especially the importance of PPMI in the interpretation of trial data. METHODS: Consecutive patients admitted to a cardiothoracic critical care unit over a 6-month period following open cardiac surgery had high-sensitivity cardiac troponin I assay performed on admission and every day for 48 h, regardless of whether there was a request by the supervising clinical team. Patients were categorized as PPMI using both the Universal Definition of Myocardial Infarction (UDMI) and Society of Cardiovascular Angiography and Interventions (SCAI) criteria. Multivariable Cox regression analysis was performed to assess whether any relationships between PPMI diagnoses and 1-year mortality were independent. RESULTS: There were 2 groups of consecutive patients: (i) after CABG ( n = 245) and (ii) after non-CABG surgery ( n = 243). Of the CABG patients, 20.4% met criteria for UDMI PPMI and 87.6% for SCAI PPMI. The diagnosis of UDMI PPMI was independently associated with 1-year mortality on multivariable Cox regression analysis [hazard ratio 4.16 (95% confidence interval 1.28–13.49)]. Of 243 patients who had non-CABG cardiac surgery, 11.4% met criteria for UDMI PPMI and 85.2% for SCAI PPMI but neither were associated with 1-year mortality. CONCLUSIONS: The incidence of SCAI PPMI in a real-world cohort of cardiac surgery patients is so high as to be of limited clinical value. In contrast, a diagnosis of UDMI PPMI post-CABG is independently associated with 1-year mortality, so may have clinical (and research) utility. Abstract : There are currently 2 guideline recommended diagnostic criteria to define periprocedural myocardial infarction (PPMI) following coronary artery bypass grafting (CABG) performed in isolation.